Gen Z’s Motives to Watch Beauty Vlogger Content : (More than just Entertainment) - New Year Haloho, Heppy; Wibowo, Tangguh Okta (POPULIKA, 2024)
Recently, following and watching content from beauty vloggers has become one of the most common activities done by Generation Z through various social media platforms. Apart from entertainment purposes, following and watching content from beauty vloggers is done with various motives and reasons. This research specifically aims to find out the motives of Generation Z in Jakarta in following and consuming content produced by beauty vloggers. This research uses a qualitative approach with a phenomenological method. The data were analyzed using Alfred Schutz's phenomenological method. The findings of this study show that there are three typification of informants in this research based on their motives: entertainment seekers, information and reference seekers and role model seekers. Keywords: Beauty Vloggers; Content; Gen Z; Motive; Phenomenology